Repurposed neglected heritage building interior architecture for commercialisation: issues and challenges - Sa’ari, Siti Nur Nabilah; Che Yusof, Muhammad Adam; Mohd Nor, Marina (UiTM Press, 2025)
This research explores the significance of heritage in conserving cultural identity, focusing on neglected heritage buildings in Malaysia, particularly Istana Bandar. Despite their deterioration, these buildings hold historical, cultural, and artistic value. Adaptive reuse, a key concept in interior architecture, involves repurposing historic buildings while preserving their structural, environmental, aesthetic, contextual, and functional integrity. The aim of this research is to investigate the possibilities of adaptive reuse approaches to protect neglected heritage buildings in Malaysia, such as Istana Bandar in Jugra, from deindustrialisation, suburbanisation, and population shifts. The study highlights several critical challenges and issues the adaptive reuse, including maintaining authenticity, high restoration costs, economic viability, balancing preservation with modernisation, sourcing replacement materials, and a shortage of skilled heritage conservation workers. Through a comparative analysis of six (6) heritage buildings, including the successful adaptive reuse of Taj Falaknuma Palace, the study identifies effective strategies such as public-private partnerships, sustainable funding mechanisms, and community involvement in conservation efforts. Findings reveal that while commercialisation can generate revenue for maintenance and preservation, it must be carefully managed to ensure cultural sustainability and prevent heritage sites from losing their authenticity. By demonstrating how interior architecture can transform neglected heritage buildings into thriving spaces, this research provides valuable insights into adaptive reuse as a viable solution for heritage conservation in contemporary contexts.